k nearest neighbor pattern match queries over spatio-temporal label trajectories - Jianqiu XU; Junxiu LIANG; Xiaolin QIN (Tongxin xuebao)
Spatio-temporal label trajectories extended traditional spatio-temporal trajectories with semantic labels.k nearest neighbor pattern match was proposed to return the k nearest trajectories that fulfilled the temporal pattern condition.The Label R-Tree (LR-Tree for short) was proposed,which appending a label table and adding label bitmap in each entry,and k nearest neighbor pattern match query algorithm based on LR-Tree was designed.Using both real and synthetic datasets,the LR-Tree was extensively evaluated in comparison with 3DR-Tree,SETI and TB-Tree.The experimental results demonstrate that LR-Tree showing better pruning ability,and verify the effectiveness of proposed algorithm and index.